Effects of gold nanoparticles on oxidative stress status in bladder cancer 5637 cells - Sajedeh Daei; Roghayeh Abbasalipourkabir; Korosh Khanaki; Fatemeh Bahreini; Nasrin Ziamajidi (Folia Medica, 2022)
Introduction: Nanomedicine has recently been known as an emerging research area with promising applications in cancer diagnosis and treatment. Aside from this, gold nanoparticles (AuNPs), as one of the important components of nanomedicine, have attracted considerable attention due to their special physicochemical properties and lower toxicity than other nanoparticles. Despite the impressive advantages of AuNPs, it has not been yet determined whether oxidative stress contributes to the toxicity of AuNPs on bladder cancer.Aim: The aim of this study was to address this issue by conducting experiments in order to investigate the effects of 20 nm AuNPs on human bladder cancer 5637 cells.Materials and methods: The viability of 5637 cells was evaluated upon 24 hour exposure to different concentrations of AuNPs (0- 50 µg/ml) by 3-(4, 5-dimethylthiazol, 2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay. In order to evaluate oxidative stress status, total antioxidant capacity (TAC), total oxidant status (TOS), malondialdehyde (MDA) and also activities of antioxidant enzymes including glutathione peroxidase (GPx), catalase (CAT) and superoxide dismutase (SOD) were all determined by colorimetric assay kits.Results: The results from our experiment showed that the cytotoxicity caused by AuNPs was dose-dependent and the IC50 value was found to be 43.14 µg/ml after 24-hour exposure. Furthermore, MDA and TOS levels were significantly increased in treated cells compared to untreated cells (p<0.05). In contrast, TAC level and the activities of SOD, GPx, CAT were significantly decreased in AuNPstreated groups as compared with the untreated cells (p<0.05).Conclusions: Overall, AuNPs decrease the cell viability and increase oxidative stress in bladder cancer 5637 cells.